Hubungan Peran Orang Tua terhadap Kejadian Perilaku Self Harm pada Remaja di SMK Negeri 4 Kota Depok - Syaiful Almunawar; Teti Rahmawati; Indah Kurniawati (Jurnal Akademika Baiturrahim Jambi, 2026)
Self-harm is the deliberate behavior of self-injury without suicidal intent, usually carried out by adolescents to cope with emotional stress or psychological problems. The role of parents in parenting, communication, and emotional support significantly influences the tendency of adolescents to commit self-harm. This study aims to determine the relationship between parental roles and the incidence of self-harm behavior in adolescents at SMK Negeri 4 Depok City. The study used a correlational design with a cross-sectional approach, involving 72 students as respondents. Data collection was carried out using a questionnaire. Self-harm measurement used a standard questionnaire, namely the Self-Harm Inventory (SHI), while parental roles were measured by a questionnaire created based on theory and journals. Data were analyzed univariately and bivariately using the Spearman rank test with a 95% confidence level. The results showed that the majority were male (76.4%), aged 16 years (59.7%), high school/vocational high school education (79.2%), did not feel the role of parents well (58.3%), and did not commit self-harm (40.3%). The Spearman rho test results showed a value of ρ = 0.000 (ρ < 0.05), which means there is a relationship between the role of parents and the incidence of self-harm behavior in adolescents at SMK Negeri 4, Depok City. This study suggests further research to explore the factors causing self-harm and the importance of health education for adolescents and parents regarding the impact and prevention of self-harm behavior.